A Geometric Approach for Robotic Arm Kinematics with Hardware Design, Electrical Design, and Implementation. (8th September 2010) - Clothier, Kurt E.; Shang, Ying
Abstract : This paper presents a geometric approach to solve the unknown joint angles required for the autonomous positioning of a robotic arm. A plethora of complex mathematical processes is reduced using basic trigonometric in the modeling of the robotic arm. This modeling and analysis approach is tested using a five-degree-of-freedom arm with a gripper style end effector mounted to an iRobot Create mobile platform. The geometric method is easily modifiable for similar robotic system architectures and provides the capability of local autonomy to a system which is very difficult to manually control.